Influence of Zinc-Saturated Zeolite on Portland Cement Hydration Kinetics - Damir Barbir; Pero Dabic (Advances in Materials Science and Engineering)
This work examines the influence of zeolite saturated with zinc (SZ) on the early hydration of Portland cement. The measurements and results indicate that the microcalorimetric method allows continuous observation and determination of SZ’s influence on kinetic processes in the early stages of hydration. According to the total heat released after 48 hours of hydration, higher SZ content results in lower heat values, while the maximum hydration occurs earlier. As SZ proportion increases, the rate of heat release and the degree of hydration decrease. Measured hydration degrees differ significantly from the calculated values when SZ is added to Portland cement, especially later in the hydration process.